The Determination of Audit Quality and its Impact on Audit Report Presentation: Empirical Study at Public Accountant Office in BEKASI City: english - Dewi Rejeki (International Journal of Business and Social Science Research, 2021)
The purpose of this study is to prove the effect of professionalism, competence, independence, and work experience of auditors on audit quality at a public accountant office in Bekasi City, which consists of senior auditors, junior auditors, partners, and supervision. The method used is a quantitative method by distributing questionnaires. The data analysis technique used is descriptive statistics and hypothesis testing. This study proves both partially and simultaneously that the professionalism, competence, independence, and work experience of auditors affect audit quality.